Petrology, geochemistry, and geochronology of mafic rocks from the Taoxinghu Devonian ophiolite, LongmuCo–Shuanghu–Lancang suture zone, northern Tibet: evidence for an intra-oceanic arc–basin system. Issue 4 (11th March 2016) - Wu, Yan-Wang; Li, Cai; Xu, Meng-Jing; Xie, Chao-Ming; Wang, Ming; Xiong, Sheng-Qing; Fan, Zheng-Guo
Abstract: A newly discovered Devonian ophiolite located in the Taoxinghu area of central Qiangtang on the Qinhai–Tibet Plateau is described. The ophiolite consists of gabbro and diabasic dikes, and invasive cumulate gabbros-leucogabbros. The ophiolite has undergone greenschist facies metamorphism and minor deformation. Dating of the metagabbro by laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) zircon U–Pb techniques yielded a weighted mean age of 367.2 ± 3.3 Ma (Late Devonian). Whole-rock geochemical analyses show that the rocks belong to the tholeiite series, with weak depletion in light rare-earth elements (LREEs), almost no Eu anomalies, weak enrichment in large-ion lithophile elements (LILEs), depletion in Nb and Ta, and weak negative Hf and Ti anomalies. These characteristics are similar to those of back-arc basin basalts. Together, these characteristics suggest that the rocks of the Devonian ophiolite formed by ~30% partial melting of spinel lherzolite, which was enriched by interaction with aqueous fluids during the late-generation phases; there is no evidence of subduction-related melting. The Devonian ophiolite rocks in the Taoxinghu area were first discovered in the LongmuCo–Shuanghu–Lancang suture zone. Detailed geochemical analyses show that the rocks formed in a back-arc ocean basin environment, indicating that the LongmuCo–Shuanghu–Lancang suture zone in central Qiangtang represents a Late Devonian intra-oceanic subduction zone in the Palaeo–Tethys Ocean. The discovery of the central Qiangtang Devonian ophiolite provides essential data for understanding the evolutionary history of the Palaeo–Tethys Ocean, and for identifying and understanding the roles of the different tectonic units on the Qinghai–Tibet Plateau.